Preliminary Study to Distinguish Sal in Rajaji Tiger Reserve through RS & GIS Technology - Shankhwar, Rajeev; Bhandari, M.S.; Meena, R.K.; Ginwal, H.S. (Indian Forester, 2019)
The forest genetic resources are taped for species distribution, mapping, demarcation, assessment of genetic diversity, population genetics study and adoption of conservation measures for protecting the species for their sustainable utilization. In the present investigation, a methodology was developed to map Sal forest areas by preparing eco-distribution maps with the help of Remote Sensing (RS) and Geographical Information System (GIS) technology. Extensive surveys were conducted in Mohand and Sukh Blocks of Chillawali Range of Rajaji Tiger Reserve during 2016–17. To distinguish the Sal forest from dry mixed deciduous forest, both blocks were divided into 58 square grids (750x750m) and total area covered by each grid was 0.5628 km2. Three to four sample plots of size 6x6m were laid out; and 80 geo-coordinates were recorded in total of 24 grids, out of which 40 geo-coordinates belongs to Sal patches. Sixty per cent Sal patches were further used to train satellite imagery (LANDSAT–8) for supervised image classification. The Google Earth was used for better visual interpretation. Maximum likelihood rule was used to discriminate between Sal forest and dry mixed deciduous forest. Accuracy assessment was carried out with the other forty per cent Sal patches. Total area of both types of forest was found to be 28.14 km2 and area covered under Sal forest was 6.28 km2. The observed Sal dominated areas is in concurrence with the management plan of Rajaji Tiger Reserve but differed from the maps of Forest Survey of India, Dehradun.